Тамбовский волк:Роман - Краснов (Черный квадрат, 1999)
Экземпляры: ф.18 (2000) / Инвентарный номер: 41848 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 78 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44